Pre-service Teachers' Perceptions of Authentic Learning in a Capstone Unit - Rebecca Spooner-Lane; Donna Tangen (Athens Institute for Education and Research, 2015)
Capstone units in higher education courses are learning experiences which are designed to bring reflection and focus to a whole course of study while, at the same time, leading students toward their entry into a new world of work (Humphrey, Brown, & Benson, 2005). The capstone experience described in this paper runs as a conference, called the Stepping Out Conference. The conference is delivered as one unit and is mandatory for all fourth year pre-service teachers. Participation in a capstone unit is an effective way for students to begin thinking of themselves as teaching professionals rather than as continuing students. Students engage in the assessment as part of their capstone experience. The assessment is designed to measure students' knowledge and skills as they relate to "authentic" real life situations (Darling-Hammond, 1991). This paper details pre-service teachers' experiences of authentic learning through their participation in a capstone unit.